The Role Of Financial Technology In Achieving Competitive Advantage In Jordanian Islamic Banks To Achieve Sustainable Development Goals - Ahmad Mohammad Ali AlJabali; Nehad Ibrahim Abd Alfatah Ineizeh; Mohammad Elayan Mohammad Alzoubi; Fuad A. Al-Bataineh (Editora Alumni In, 2025)
Non Indexed Publication (Tier 4)